Dynamic Contrast-Enhanced MRI Findings of Acute Pancreatitis in Ectopic Pancreatic Tissue: Case Report and Review of the Literature - Thangasamy, Senthur J; Zheng, Larry; Mcintosh, Lacey; Lee, Paul; Roychowdhury, Abhijit (JOP. Journal of the Pancreas, 2014)
Context Acute pancreatitis in ectopic pancreatic tissue is an uncommon cause of acute abdominal pain and can be difficult to diagnose on imaging. Our aim is to raise awareness and aid in the diagnosis of this entity by highlighting helpful dynamic contrast-enhanced MRI imaging findings. Case report We report a 51-year-old man with acute onset epigastric pain presented to ER. With the presence of elevated serum lipase, the clinical diagnosis of acute pancreatitis was made. Contrast enhanced CT demonstrated normal pancreas and a focal mass at the duodenojejunal flexure, mimicked a neoplasm. Subsequent dynamic contrast enhanced MR images demonstrated enhancement pattern of the lesion similar to the native pancreatic tissue enhancement, a finding raised the possibility of acute pancreatitis in ectopic pancreatic tissue, but tumor was not excluded. Finally, patient undergone surgical bowel resection including the suspected mass that was proved as an ectopic pancreatic tissue on microscopic examination. Conclusion We concluded that findings on dynamic contrast enhanced MR imaging can be characteristic and diagnostic of acute pancreatitis in ectopic pancreatic tissue in the appropriate clinical setting. Image: Low power view of the jejunal mass biopsy.